Kashmir : exposing the myth behind the narrative - Khalid Bashir Ahmad (New Delhi: Sage Publications)
"The advent of Islam in medieval Kashmir gave birth to a narrative that describes forcible mass conversion of Hindus, eviction of aborigines and wanton demolition of religious symbols. A minority of Kashmiri Brahmans and their progeny who did not convert to Islam built and successfully perpetuated this narrative over the centuries. In the course of time, new elements were added to it. Following the eruption of armed insurgency in Kashmir and mass migration of Kashmiri Pandits in 1990, this community narrative has turned into the Indian mainstream view on Kashmiri Pandits. Kashmir : Exposing the Myth behind the Narrative challenges the existing narrative through historical facts and cross-referencing. It exposes many fallacies used to uphold this narrative and dissects the work of historians that has sustained ahistorical perceptions over a long period of time. The book links history to the present and facilitates an understanding of the situation today"--Provided by publisher.
Keywords: Myth India; Kashmiri Pandits; Historiography Jammu and Kashmir; History Jammu Kashmir; History India; History